Uptake of tetracycline and metabolites in Phragmites australis exposed to treated poultry slaughterhouse wastewaters - Topal, E. Isil Arslan (Elsevier Science Bv, 2015)
In this study, the uptake of tetracycline (TC) and metabolites (ETC, EATC and ATC) by Phragmites australis naturally grown in a stream (Hinsor stream, Turkey) that takes the treated wastewaters of a poultry slaughterhouse was investigated. Furthermore, the occurrence and fate of TC and metabolites were also investigated in the stream. The decreasing uptake order of TC and metabolites by P. australis was root > stem > leaf. The determined concentrations of TC and metabolites in roots and stems were followed the decreasing order of EATC > ATC> ETC> TC. The uptake order of TC and metabolites in leaves was ATC > EATC > ETC > TC. The highest TC, ETC, EATC and ATC concentrations in surface water (SW) samples were obtained as 2.37 +/- 0.11, 3.96 +/- 0.19, 21.3 +/- 1.0 and 11.2 +/- 0.5 mu g/L, respectively. The highest TC, ETC, EATC and ATC concentrations in sediment samples were obtained as 9.69 +/- 0.48, 27.0 +/- 1.3, 13.9 +/- 0.69 and 23.0 +/- 1.11 ppb, respectively. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: P. australis; Tetracycline; Metabolites; Uptake; Poultry; Chicken